Multidrug resistance among biofilm-forming uropathogens isolated from catheter-associated urinary tract infection from a rural tertiary care center in Eastern India. - Paul, Retina; Saha, Priyanka; Pal, Kuhu; Kapoor, Avi; Sinha, Arpita; Roy, Joydip (International Journal of Endorsing Health Science Research, 2024)
Background: Urinary tract infections (UTIs) are prevalent nosocomial infections, accounting for 30-40% of hospital-acquired infections. Indwelling urinary catheters create conducive environments for biofilm formation, limiting antimicrobial diffusion and facilitating the transfer of antimicrobial resistance genes. Multidrug resistance (MDR) among biofilm-forming uropathogens poses significant therapeutic challenges. This study aimed to assess the prevalence of MDR among biofilm-forming uropathogens in catheter-associated UTIs (CAUTIs) and characterize their antimicrobial resistance patterns. Methodology: The study included 95 catheterized patients over six months. Uropathogens were isolated and identified using standard methods. Biofilm production was assessed using tissue culture plates, tube tests, congo red agar, and modified congo red agar methods. The antibiotic resistance profiles of biofilm producers and non-producers were determined. Results: The prevalence of CAUTIs was 68.42%, with Escherichia coli being the most common uropathogenic (43.07%). Among the 65 isolates, 58.46% were identified as biofilm producers using four different methods. Biofilm producers exhibited higher resistance compared to non-producers, particularly against ampicillin (100% vs. 82.35%), Amoxiclav (90.62% vs. 58.82%), and cotrimoxazole (90.62% vs. 70.58%). Multidrug resistance was significantly higher among biofilm producers (80.64%) than non-producers (38.88%). Conclusion: The study highlights a high prevalence of biofilm formation among CAUTIs patients, contributing to antibiotic resistance. Multidrug resistance among biofilm producers exacerbates therapeutic challenges for clinicians. Strict aseptic techniques during catheterization are crucial to prevent infections by multidrug-resistant biofilm-forming uropathogens. Regular updates to institutional empirical therapy protocols are necessary to mitigate recurrence and treatment failure in UTI cases.